Analisis Iklim Komunikasi Organisasi pada Travel Agent Real Bali Holidays - Ni Made Ayu Andriani Ratu Bulan; Anak Agung Ngurah Eddy Supriyadinata Gorda; Melati Budi Srikandi; Decky Cipta Indrashwara (Lembaga Pengembangan Kinerja Dosen, 2026)
This research is motivated by the highly competitive dynamics of the tourism industry in Bali, which demands effective internal coordination. The study aims to analyze the organizational communication climate implemented at Travel Agent Real Bali Holidays, focusing on the aspects of openness, effectiveness, and communication sustainability. The research method used is qualitative descriptive, with data collection techniques through non-participatory observation, semi-structured interviews, and document studies. Research informants were determined using purposive sampling from management, employees across various divisions, and external partners. The results indicate that the organizational communication climate at Real Bali Holidays is flexible and adaptive to operational needs. Communication openness is evident from the space provided for organization members to convey ideas and constraints without rigid structural barriers. Communication effectiveness is supported by the use of integrated communication channels that ensure message clarity and minimize misunderstandings. Communication sustainability is maintained through consistent interaction patterns in daily work activities, although most practices remain informal. These findings emphasize that a conducive communication climate plays a vital role as the foundation for cross-divisional work coordination. The implication of this research is the need to strengthen the communication system through formal procedure standardization to support organizational sustainability amidst industry competition.